Lines of thought central concepts in cognitive psychology - Rips, Lance J. (New York ; Oxford : Oxford University Press, 2011)
How can we think about maths, despite the immateriality of numbers, sets, and other mathematical entities? How are we able to think about what might have happened if history had taken a different turn? Questions like these turn up in nearly every part of cognitive science and are central to our human position of having limited knowledge of what is true.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Jan. 10, 2011).
Keywords: Cognitive psychology